Social structure of a population of bottlenose dolphins (Tursiops truncatus) in the oceanic archipelago of Madeira, Portugal - Dinis, Ana (2021)
In order to investigate social structure, 11 years of individual photo-identification data of bottlenose dolphin were analysed. We examined the type of association indices between pairs of identified individuals; the patterns of affiliation between indi vidual dolphins and the probabilities of association between individuals over time. Between 2001 and 2012, there were 272 encounters which resulted in the identification of 501 individuals. The discovery curve resulting from the photo-identification analysis indicated an open population with regular recruitment of new individuals. All individuals were found to be asso ciated at an association index of ,0.05. A total of 291 individuals recorded from 2004 to 2012 were used to assess the tem poral pattern of the social structure. The model fit to the Standardized Lagged Association Rate (SLAR) that best described the studied bottlenose dolphin population was ‘casual acquaintances’, and the analysis of associations over time showed a decreasing SLAR curve that falls until reaching the null rate, confirming random associations. The decline of the SLAR curve after 500 days (1.4 years) suggests disassociation over that time period which can be explained by demographic events such as mortality or emigration. In an open ocean habitat like Madeira this is not unexpected, as there are neither geographic boundaries nor enclosed environments. This population presented a dynamic and fluctuating social structure, where groups change in size and composition. In future conservation efforts this population should be considered as one large community, where individuals associate, disassociate and reassociate with each other over time.